The Relationship Between Knowledge Level about Physical Activity and Depression Among Pre-Elderly Individuals - Naswa Aulianisa; Upik Rahmi; Dhika Dharmansyah (Universitas Negeri Semarang, 2025)
This study aims to determine the relationship between knowledge about physical activity and depression in the pre-elderly group in the working area of the Ledeng Community Health Center (Regional Technical Implementation Unit), Bandung City. The method used is a descriptive correlational study with a cross-sectional approach, where data is collected over a period of time. The study sample consisted of 50 pre-elderly people aged 45–59 years selected using accidental sampling techniques. The instruments used included a questionnaire on the level of knowledge of physical activity and the Beck Depression Inventory-II (BDI-II). Data were analyzed descriptively and inferentially using the Chi-Square test with a significance level of p < 0.05. The results showed that the majority of respondents had good knowledge of physical activity (56%) and experienced minimal depression (82%). Statistical tests showed a relationship between knowledge of physical activity and levels of depression in the pre-elderly (p = 0.000). These results indicate that the better the pre-elderly people's understanding of physical activity, the less prone they are to developing depression. Thus, efforts to improve health education regarding the importance of physical activity need to be strengthened as a strategy to prevent depression and improve well-being in the pre-elderly group.